KEBERADAAN PARTAI POLITIK YANG TIDAK DIKETAHUI MENELUSURI FUNGSI PARTAI POLITIK DI INDONESIA PASCA SOEHARTO - Dian Iskandar (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
This paper aims to examine the existence of political parties in Indonesia by looking at the roles and functions carried out by political parties. Data collection method used is study desk. the results are known that the presence of political parties is not felt by the public because the political party has not run the standard functions that diembannya with the maximum and so as to give a tendency of public disappointment against political parties, so that for the political party community is merely a democratic attribute only.